ON THE NUMERICAL SIMULATION OF THE EFFECT OF DISEASE TRANSMISSION COEFFICIENT ON SEIR EPIDEMIC MODEL USING HYBRID BLOCK METHOD - Kolawole, Mutairu (JURNAL DIFERENSIAL, 2024)
This work contains the study, analysis, and solution of a SEIR epidemic model. An effective hybrid block method was used in the solution of the system of linear differential equations to investigate the effect of transmission coefficient on the SEIR model with a permanent immunity. Numerical simulation of the included control parameters are carried out. The obtained results and outcomes are presented graphically.